The Effect of Capital Structure, Profitability, Free Cash Flow, and CAR Indonesian Banking Firm Value - Irananda Sihombing; Erlina Erlina; Keulana Erwin (International Forum of Researchers and Lecturers, 2026)
The purpose of this study is to examine and analyze whether capital structure, profitability, free cash flow, and capital adequacy ratio affect firm value with managerial ownership as a moderating variable in conventional banking companies listed on the Indonesia Stock Exchange for the period 2022-2024. This study was conducted based on information obtained from the Indonesia Stock Exchange. The sampling technique used was purposive sampling. The population in this study consisted of all conventional banking companies listed on the Indonesia Stock Exchange for the period 2022-2024, with a sample of 17 companies and 51 total observations. Hypothesis testing was carried out using panel data regression analysis with the EViews application. The results of this study indicate that capital structure, profitability, free cash flow, and capital adequacy ratio do not have a significant effect on firm value. Furthermore, managerial ownership is unable to moderate the effect of capital structure, profitability, free cash flow, and capital adequacy ratio on firm value in conventional banking companies listed on the Indonesia Stock Exchange for the period 2022-2024.